Trends in Library Services and the Competencies of the Librarian - Karina Lira Da Silva, Edna; dos Santos, Andrey Anderson; Maria dos Santos Bahia Jacintho, Eliana; Marques Chaíça, Beatriz (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2024)
This study sought to discuss the perspective of services for libraries and to indicate the competences of professionals to act in face of this scenario. Regarding the nature of the research, it is characterized as basic research, using an exploratory approach and bibliographic and documental characteristics. The searches were carried out in the following databases: Web of Science, Scopus (Elsevier), SciELO. The 2,030 documents were retrieved; these were explored by reading the titles, the keywords, and the abstract. In this way, we evaluated which of the articles answered the research question. Among the documents checked, 55 documents were selected. The results identified services in the technological sphere: Artificial Intelligence (AI), the Internet of Things, Drones, Virtual Assistants, and Blockchain. In the society, sphere Co-working. In the Education category, Badging, and in the Environment category, Resilience. Given what was proposed, the librarian’s perception of these changes becomes essential as actors and providers of these services.